Performance of wireless local area networks in Malaysian institutions - Abdul Aziz, Azrilah; Suhaimi, Mohd Adam (JITI, 2004)
Although Wireless Local Area Networks (WLANs) are widely used in many settings little work has been done in studying their impact and benefits. This study provides empirical indicators on the performance of the WLANs implemented on Malaysian Institutions of Higher Learning Our research adopted Deming’s P-D-C-A Model and modified it to Plan-Implement-Control-Evaluate (P-I-C-E) in establishing a performance measurement for a WLAN; hence WLAN Performance Index (WPi). The measurement consists of four key performance indicators (KPi), reflecting the performance of the four P-I-C-E dimensions. These performance indicators provide a guide for the institutions to take the necessary corrective and preventive actions in attaining an effective WLAN system. Benchmarking was conducted by comparing three institutions in identifying the best WLAN system measures. The WPi is then applied to the three Malaysian public institutions of higher learning (MIPTA), which have implemented such WLAN system. The study reveals the WPi of each of the MIPTA being measured, indicating the strength and weaknesses of each institutions. Also, we suggest corrective actions necessary in achieving an effective and efficient WLAN system. Gap analysis was done to the three MIPTAs findings comparative to the benchmarked WLAN system.